VULNERABILITY OF GROUNDWATER IN QUATERNARY AQUIFERS TO ORGANIC CONTAMINANTS: A CASE STUDY IN WUHAN CITY, CHINA - Wang Ya.; Merkel B.J.; Li Y.; Ye H.; Fu S.; Ihm D. (My University, 2007)
More than 30 organic contaminants were detected in shallow groundwaters at Wuhan, the largest city in central China. Seriously contaminated groundwaters were from densely populated, industrial and commercial areas. Abnormal concentrations were found in groundwater from Hankou, downtown Wuhan: trimethylbenzene up to 29 μg/L, tetramethylbenzene up to 866 μg/L, and trichloroethene up to 9.5 μg/L. Benzene, Toluene, Ethylene and Xylene (BTEX) contamination of groundwater is serious and widespread at Wuhan, ranging between 0.14 and 25.0 μg/L. Considering the hydrogeological conditions of most Chinese cities, DRAMIC, a modified version of the widely used DRASTIC model, was proposed by the authors for assessing vulnerability of groundwater to contamination. The factors D, R, A and I in DRAMIC model are the same as in DRASTIC. The factor topography is ignored. The factor soil media is substituted by a new factor aquifer thickness (M) and the factor hydraulic conductivity of the aquifer by a new factor impact of contaminant (C). The equation for determining the DRAMIC Index is: DRAMIC = 5D R + 3R R + 4A R + 2M R + 5I R + 1C R. The calculated DRAMIC Index can be used to identify areas that are more likely to be susceptible to groundwater contamination relative to each other. The higher the DRAMIC Index is, the greater the groundwater pollution potential. Applying DRAMIC, a GIS-based vulnerability map for Wuhan city was prepared. Interestingly, places such as downtown Hankou, where enhanced concentrations of BTEX have been detected, correspond quite well with those with higher DRAMIC ratings.
Keywords: URBAN GROUNDWATER; VULNERABILITY ASSESSMENT; ORGANIC CONTAMINATION; GEOGRAPHIC INFORMATION SYSTEM; CHINA; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная